Beating the Fascists? The German Communists and Political Violence, 1929-1933 - Kitchen, Martin (Labour / Le Travail, 1985)
This article reviews the book, "Beating the Fascists? The German Communists and Political Violence, 1929-1933," by Eve Rosenhaft.
Keywords: DOCHERTY; Charles; Nonfiction; REVIEWS; STEEL & Steelworkers: The Sons of Vulcan (Book); Steel industry; books